The catch : a Joe Gunther novel - Mayor, Archer (Mayor, Archer. Joe Gunther novel., 2008)
Joe Gunther gets the call that every law enforcement person hates and every friend and family member of a policeman fears<U+2013>-a cop has been murdered in the line of duty. Deputy Sheriff Brian Sleuter has been shot to death during a routine traffic stop on a dark country road. From what can been seen on the cruiser<U+2019>s tape recorder of the killers, it is believed that they are a couple of Boston-based drug runners who were stopped by the deputy on their way from Canada down to Boston. That brings Gunther and his major crimes team into the investigation<U+2015>-and eventually to Alan Budney, the disaffected son of a Maine lobsterman, now a drug kingpin, who uses the closed, clannish lobster fishing community, and his extended family in particular, to move drugs along the New England coast.